2011
DOI: 10.4028/www.scientific.net/amm.130-134.3799
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Release Characteristics of Chlorine and Alkali Metal during Co-Firing of Wheat Straw and Lean Coal

Abstract: Experiments were carried out on a tubular furnace. The results showed that the released amount of K and Cl increased with the wheat straw share of the blends, meanwhile the released amount of Cl was far more than that of K. Al and Si from coal can capture K to form KAlSixOy, which would promote the release of HCl. The activity of Al and Si increased with the temperature rising. During combustion, Ca and Mg can react with Al and Si, resulting in an increased release of K and a decreased release of HCl indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…12,14,16,17 In addition, experiments have indicated that combustion of a mixture of two fuels enhances the release of chlorine while lowering the release of potassium, as compared to the release profiles observed during combustion of the individual fuels. 13,18 Figure 1 outlines the principle of oxy-fuel combustion. The atmosphere present in oxy-fuel combustion differs from that in air combustion because of the replacement of nitrogen with recycled flue gases.…”
Section: ■ Oxy-fuel and Co-combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,16,17 In addition, experiments have indicated that combustion of a mixture of two fuels enhances the release of chlorine while lowering the release of potassium, as compared to the release profiles observed during combustion of the individual fuels. 13,18 Figure 1 outlines the principle of oxy-fuel combustion. The atmosphere present in oxy-fuel combustion differs from that in air combustion because of the replacement of nitrogen with recycled flue gases.…”
Section: ■ Oxy-fuel and Co-combustionmentioning
confidence: 99%
“…Furthermore, the ash components, which include silicon, calcium, phosphorus, aluminum, and iron, derived from the second fuel (e.g., coal) influence the levels of chlorides formed in the boiler. , Studies performed with various fuels and fuel mixtures have shown that the amount and composition of the ash as well as the mixing and temperature conditions of the boiler affect the percentage of inorganic matter released as gaseous compounds during combustion. Aluminosilicates, which are found as ash components of coal, have been suggested to be the main binders of alkali chlorides to ash during co-combustion when the share of coal is large. However, other silicates that are commonly present in biofuels also have important roles, depending upon the mixture of fuels used. ,,, In addition, experiments have indicated that combustion of a mixture of two fuels enhances the release of chlorine while lowering the release of potassium, as compared to the release profiles observed during combustion of the individual fuels. , …”
Section: Oxy-fuel and Co-combustionmentioning
confidence: 99%